A pyridine-based conjugated imprinted polymer as an adsorptive photocatalyst for efficient removal of aqueous Cr(vi). Issue 14 (27th January 2023) - Guo, Zhipeng; Wei, Wei; Li, Yihang; Li, Jin; Zhang, Xiaoke; Hou, Fengming; Wei, Ang
Abstract : A designed pyridine-based ion-imprinted polymer was constructed by introducing 4-vinylpyridine via an in situ copolymerization reaction, which exhibited impressive Cr(vi ) adsorption performance and high efficiency for photocatalytic Cr(vi ) reduction. Abstract : Herein, a designed pyridine-based conjugated imprinted polymer (CIP) was constructed by introducing 4-vinylpyridine (4-VP) via an in situ copolymerization reaction. In addition to the good adsorption performance of Cr(vi ), this polymer also showed high efficiency in reducing Cr(vi ) in water by photocatalysis. The ingenious design of the polymer not only furnished insight into the enhanced photocatalytic reaction kinetics but also provided a new route for the modification of the molecular skeleton of the conjugated polymer photocatalyst.